Factors affecting consumer engagement on online social networks: self-congruity, brand attachment, and self-extension tendency - Rabbanee, Fazlul; Roy, Rajat; Spence, Mark (Emerald, 2020)
This paper examines a chain of relationships running from self-congruity with a brand—that can stem from the actual, ideal or social self—to brand attachment, and from there to consumer engagement on social networking sites, specifically liking, sharing, and commenting. It further advances self-extension tendency as a moderator affecting the link between self-congruity and brand attachment. Two studies were conducted to test four hypotheses. Study one (n = 282) engaged a self-administered survey with students at a large Australian university. The second study (n = 342) was conducted amongst the members of an Australian online panel, and thus enhances generalizability. The findings reveal that activated self-congruity orientations are brand-specific. Both studies reveal that two of the three self-congruity orientations affect brand attachment, which in turn influences consumers’ proclivity to like, share, and comment on Facebook. Moreover, it has been found that when self-extension tendency is high, it strengthens the relationship between a self-congruity orientation and brand attachment. These findings extend existing theory in three ways: they show 1) social self-congruity affects brand attachment in online contexts, 2) brand attachment is a mediating variable affecting pro-brand social networking behaviours, and 3) self-extension tendency moderates the relationship between self-congruity and brand attachment. Social networking sites are widely acknowledged as a key marketing channel affecting both pre- and post-purchase behaviours; hence, these insights have theoretical as well as practical relevance.